Analysis of antioxidant and standardization of ethanol extract of rumput mutiara (Oldelandia corymbosa L.) - Herawati, Irma Erika; Saepudin, Syumillah (Universitas Ahmad Dahlan, 2025)
The majority of traditional medicinal plants in Indonesia lack scientific validation. Scientific assessment, in conjunction with traditional knowledge, is crucial for acquiring effective pharmaceuticals for commercial use. Rumput mutiara (Oldelandia corymbosa L) is a member of the Rubiaceae family and has been utilized as a traditional medicinal plant for the treatment of various ailments. The objective of this research was to assess the quality of both specific and non-specific parameters and to investigate the antioxidant potential of rumput mutiara. Antioxidant activity was evaluated with 2,2-diphenyl-1-picrylhydrazy (DPPH). The findings for non-specific parameters indicated that the shrinkage drying of the extract and the water content were 18.00 ± 0.000% and 12.20 ± 0.000%, respectively. Simultaneously, particular parameters indicate that the extracts possess a distinct odor, exhibit a blackish-brown hue, and display a viscous consistency. Microscopic parameters of rumput mutiara simplicia showed fragments such as anthers, leaf mesophyll, epidermis and stomata, transport bundles, stem parenchym, and sclerenchyma. Spesific parameters, such as the water-soluble content, and ethanol-soluble compounds were 72.00 ± 0.000 % and 35.00± 0.000 % , respectively. In addition, TLC profiles showed that secondary metabolites of extract were 6 alkaloids, 5 phenolics, 5 flavonoids, 5 tanins, 3 saponins, 5 steroid, and 5 glycosides. The extract has strong antioxidant activity with IC50 value of 14.11 ±0.008 µg/mL.